Cooperação intersistêmica em apoio à educação profissional e tecnológica - Oliveira, Eduardo Mendes de (2009)
Several computer applications to support education have been continuously implemented on a separate and isolated way. In this context, the collaboration can extrapolate the interpersonal relationship and include the interaction between resources, allowing different tools to cooperate in carrying out relevant functions to the process of teaching and learning. There is currently an effort to build interoperable tools and content that can be reused and shared, given the high cost and complexity of the production of these resources, so that can be added towards the development of more complete and comprehensive tools. Among the approaches to systems integration, the service-oriented computing appears as the most used. In that sense, this dissertation examines aspects related to the integration of tools developed to support the teaching and learning process and presents the design, modeling and implementation of a service-oriented environment for InterRed, a repository of educational digital content, or Learning Objects (LOs), specifically designed for the Federal Network of Vocational and Technological Education. In order to prove the effectiveness of these integration resource, a solution that allows the Virtual Learning Environment Moodle to use the services developed for the InterRed has been developed.